Preparation of zeolite nanocrystals via hydrothermal and solvothermal synthesis using of rice husk ash and metakaolin - Setthaya N. (2017)
© 2016 Trans Tech Publications, Switzerland. Synthesis of zeolite nanocrystals from rice husk ash and metakaolin was studied. Hydrothermal and solvothermal methods at 120 °C for 6 h were used as comparative study. Starting mixes were prepared with SiO 2 /Al 2 O 3 molar ratio of 4. Two factors; stirring time before hydrothermal and solvothermal treatments and solvent types were studied. The synthesized products were characterized in terms of mineralogy using X-ray diffraction, specific surface area using N 2 adsorption and desorption isotherm, morphology and composition using scanning electron microscopy and electron dispersion X-ray analysis. The results showed that faujasite and zeolite P1 were obtained from both of hydrothermal and solvothermal methods. However, crystals sizes of the synthesized zeolites from solvothermal method were smaller than that of hydrothermal method in that 100-300 nm and 100-1500 nm for solvothermal and hydrothermal methods, respectively. Specific surface area of the zeolites obtained from hydrothermal and solvothermal methods were 418 and 487 m 2 /g, respectively.